Generation of an induced pluripotent stem cell line from an unaffected female whose two sisters suffered spontaneous coronary artery dissections (SCAD) (VCCRIi024-A) - Monique Bax; Keerat Junday; Emily Hurley; Stephanie Hesselson; Lucy McGrath-Cadell; Xenia Kaidonis; Ingrid Tarr; Eleni Giannoulatou; Siiri E. Iismaa; Robert M. Graham (Stem Cell Research, 2025)
Spontaneous Coronary Artery Dissection (SCAD) is a poorly understood predominantly female condition that can cause myocardial infarction, often affecting otherwise healthy women. Here, we generated an induced pluripotent stem cell line from a female with two SCAD-affected sisters. This individual has not had a SCAD to date; she is currently 12 years older than when SCAD first manifested in her sisters. This resource provides a valuable control for investigating mechanisms underlying SCAD susceptibility.